Strategic leadership: how to think and plan strategically and provide direction - Adair, John Eric (London : Kogan Page, 2010)
A strategic leader is essentially the leader of any organization and someone who has to steer the company in times of change, whilst motivating and inspiring their team.
Include index.
Keywords: Leadership; Executive leadership